Peptide Shuttles for Blood-Brain Barrier Drug Delivery - Macarena Sánchez-Navarro; Ernest Giralt (MDPI AG, 2022)
The blood-brain barrier (BBB) limits the delivery of therapeutics to the brain but also represents the main gate for nutrient entrance. Targeting the natural transport mechanisms of the BBB offers an attractive route for brain drug delivery. Peptide shuttles are able to use these mechanisms to increase the transport of compounds that cannot cross the BBB unaided. As peptides are a group of biomolecules with unique physicochemical and structural properties, the field of peptide shuttles has substantially evolved in the last few years. In this review, we analyze the main classifications of BBB-peptide shuttles and the leading sources used to discover them.